PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SDN 03 KOTO BARU - dedi, Aprima; Filahanasari , eka; Purmala Sari, Elvi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the suboptimal state of Indonesian language learning, low student interest in writing, and students' inability to express ideas or thoughts in written form. This situation is further evidenced by Mid-Semester Assessment (PTS) scores that remain unsatisfactory, with many students scoring below the Minimum Completeness Criteria (KKM). To address this issue, the researcher conducted a study utilizing the Flipped Classroom learning model. This study aims to determine the effect of the Flipped Classroom model on the topic